Linking mentoring program to self-efficacy as a predictor of mentee outcomes - Ismail, Azman; Mohd Shariff, Mohd Noor; Kho, Michael Khian Ju; Sahol Hamid, Norashikin (Medwell Journals, 2012)
The purpose of this study is to examine the influence of self-efficacy in the relationship between mentoring program practices and mentee outcomes using 196 usable questionnaires collected from students studying in institutions of higher learning in Sarawak, Malaysia.The outcomes of stepwise regression analysis showed two important findings; firstly, the relationship between self-efficacy and mentoring program practices (i.e., communication, participation and support) is insignificantly correlated with psycho social. Secondly, the relationship between self-efficacy and mentoring program practices (i.e., communication, participation and support) is significantly correlated with academic performance. Statistically, this result confirms that the relationship between self-efficacy and mentoring program practices has not been an important predictor of psycho social but the relationship between self-efficacy and mentoring program practice has been an important predictor of academic performance in the organizational sample.